Regulation of Tissue Immune Responses by Local Glucocorticoids at Epithelial Barriers and Their Impact on Interorgan Crosstalk - Merk, Verena M.; Phan, Truong San; Brunner, Thomas (Frontiers in Immunology, 2021)
is of increasing interest with regard to the search for alternatives to synthetic corticosteroids in the therapy of inflammatory disorders. Despite being very effective in many situations the use of synthetic corticosteroids is often controversial, as exemplified in the treatment of influenza patients and only recently in the current COVID-19 pandemic. Exploring the regulatory capacity of locally produced GCs in balancing immune responses in barrier tissues and in pathogenic disorders that lead to symptoms in multiple organs, could provide new perspectives for drug development. Intestine, skin and lung represent the first contact zones between potentially harmful pathogens or substances and the body, and are therefore important sites of immunoregulatory mechanisms. Here, we review the role of locally produced GCs in the regulation of type 2 immune responses, like asthma, atopic dermatitis and ulcerative colitis, as well as type 1 and type 3 infectious, inflammatory and autoimmune diseases, like influenza infection, psoriasis and Crohn’s disease. In particular, we focus on the role of locally produced GCs in the interorgan communication, referred to as gut-skin axis, gut-lung axis or lung-skin axis, all of which are interconnected in the pathogenic crosstalk atopic march.